IMPORTANT ASPECTS OF FRUSTRATION TOLERANCE IN PERSON (Ustozlar uchun, 2024)
Today, there are many definitions of the concept of “frustration”. For example, the following definition is given in the psychological dictionary: frustration (Latin frustratio - to deceive, to wait in vain) - a mental state that occurs as a result of not being able to satisfy a need or desire. In the dictionary of psychological analysis, frustration is defined as a state resulting from experiences of the impossibility of achieving set goals and satisfying desires, plans and expectations [5].